THE INFLUENCE OF HALAL LOGO COSMETIC PRODUCTS ON PURCHASING DECISIONS FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Alrusjdah, Sabiqah Insani; Purnomo, Agus; Zahra Maulida, Atika (Jurnal Al-Iqtishad, 2023)
The reason for this study was to determine the impact of halal marks on superficial item-buying choices for all UNISKA Muhammad Arsyad Al Banjari understudies. This exploration was directed at the UNISKA Muhammad Arsyad Al Banjari grounds in Banjarbaru. In this review, the subject of exploration was UNISKA understudy Muhammad Arsyad Al Banjari, while the object of examination was the impact of halal marks on surface-level item buy choices for all UNISKA Muhammad Arsyad Al Banjari understudies. This kind of examination is a quantitative exploration because the consequences of the information got are an assortment of numbers, utilizing a straightforward direct relapse investigation strategy. This exploration was directed on UNISKA understudy Muhammad Arsyad Al Banjari with a complete example of 97 female students. The consequences of this study show that the Halal Mark fundamentally affects buying choices. This should be visible from the huge Halal Logo of 0.000, which implies more modest than the degree of importance utilized, which is 0.05, and can likewise be seen from the account of 12.220, which implies the t count is more prominent than the t table of 1.985.